A POLLINATOR-FRIENDLY, COST-EFFECTIVE MANGO HOPPER MANAGEMENT STRATEGY DEVELOPED BASED ON PEST BEHAVIOR - HAMEED, A; KHAN , AH; REHMAN , AU; MUHAMMAD , N; IQBAL , A; MUSTAFA , G; AHMAD , M; HUSSAIN, R; KHIZAR, M; BIBI , F; HUSSAIN, M; IMRAN , M (Biological and Clinical Sciences Research Journal, 2024)
The mango hopper is the most destructive pest of the mango crops. If unmanaged, this pest may decrease 80-100 % of crops. Hence, we designed a strategy to manage the hoppers based on the timing of the pest activity and the pest abundance peaks at different times of the year. The experiment was conducted in the experimental orchards of the Mango Research Institute Multan Punjab, Pakistan, from 2023 to 2024 in a density mango orchard. Three insecticides (dinotefuran, clothianidin, and flonicamid) were sprayed in various treatments, viz., summer spray only on the stem, winter spray on the only stem, post-harvest application (whole tree spray), summer prays only on stem + post-harvest spray, post-harvest spray + winter spray, summer + post-harvest + winter spray against the mango hopper. Overall, the mango hopper population was deficient in the treatment where the spray was done (one in summer, 2nd at the post-harvest stage (whole tree spray) and 3rd spray was done in winter on tree trunks only. The pest population was observed in the morning (8:00 am), mid-day ( 1:00 P.m.), and evening (6:00 PM) on leaves and tree trunks. During summer months, the population was higher on tree trunks at 1:00 pm, while in the winter, at 1:00 pm, the population was higher on the leaves. In the morning and evening, on tree canopy, the population is higher in the summer and lower in the winter. The population is higher on the stem in the morning and evening in winter. Hence, one spray in the summer on the tree trunk at 1:00 pm, 2nd whole tree spray after fruit harvest and a third spray during winter on tree trunks in the morning or evening minimised pest population during the fruiting season. Farmer yield and income are greatly enhanced with this strategy.